2012
DOI: 10.17221/257/2011-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the rheological behaviour of enzyme clarified lime (Citrus aurantifolia L.) juice concentrate

Abstract: Manjunatha S.S., Raju P.S., Bawa A.S. (2012): Modelling the rheological behaviour of enzyme clarified lime (Citrus aurantifolia L.) juice concentrate. Czech J. Food Sci., 30: 456-466.The rheological behaviour of enzyme clarified Lime (Citrus aurontifolia L.) juice was studied as a function of the total soluble solid (TSS) content (7.3-55.7°Brix), corresponding water activity (a w ) (0.985-0.831) at different temperatures o C) using co-axial controlled stress rheometer. The rheological parameter shear stress w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
(28 reference statements)
6
11
0
Order By: Relevance
“…Similar type of exponential relation was reported relating to flow activation energy to total soluble solid content. The magnitude of the coefficient concentration was found to be 0.049 and it was within the range as reported for different fruit juices such as pomegranate, pineapple, cherry, peach, chokeberry, lime, gooseberry and tender coconut water (Altan and Maskan 2005;Kaya and Sozer 2005;Shamsudin et al 2007;Giner et al 1996;Ibarz et al 1992a;Juszczak et al 2009: Manjunatha et al 2012a2012b;Manjunatha and Raju 2013). It was reported that flow activation energy increased significantly with square of total soluble solid content for blue berry and raspberry juices, where as it increased quadratically with soluble solid content in case of liquorice (Glycyrrhiza glabra ) extract (Nindo et al 2005;Maskan 1999).…”
Section: Effect Of Temperaturesupporting
confidence: 81%
See 4 more Smart Citations
“…Similar type of exponential relation was reported relating to flow activation energy to total soluble solid content. The magnitude of the coefficient concentration was found to be 0.049 and it was within the range as reported for different fruit juices such as pomegranate, pineapple, cherry, peach, chokeberry, lime, gooseberry and tender coconut water (Altan and Maskan 2005;Kaya and Sozer 2005;Shamsudin et al 2007;Giner et al 1996;Ibarz et al 1992a;Juszczak et al 2009: Manjunatha et al 2012a2012b;Manjunatha and Raju 2013). It was reported that flow activation energy increased significantly with square of total soluble solid content for blue berry and raspberry juices, where as it increased quadratically with soluble solid content in case of liquorice (Glycyrrhiza glabra ) extract (Nindo et al 2005;Maskan 1999).…”
Section: Effect Of Temperaturesupporting
confidence: 81%
“…The magnitude of coefficient (b) of water activity was found to be −12.985 in case enzyme clarified sapota juice. The magnitude of power law coefficient (b) of variation with flow activation energy with water activity is comparable with values of lime juice and tender coconut water (Manjunatha et al 2012a;Manjunatha and Raju 2013).…”
Section: Effect Of Temperaturesupporting
confidence: 62%
See 3 more Smart Citations